RESCHEDULING SEBAGAI UPAYA PENYELESAIAN KREDIT MACET PADA PERJANJIAN KREDIT PEMILIKAN RUMAH (KPR) ANTARA DEBITUR PADA PT. BANK RAKYAT INDONESIA (Tbk) KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The realization of people's welfare is characterized by an increase in decent and dignified life and sufficient basic needs, namely food, clothing, shelter, health, education and employment. Houses are basic needs and have functions that are very important for human life. To own a house, not all groups of low and middle income people. Bank Rakyat Indonesia is one of the state banks appointed to implement a housing loan program with its credit facility called Bank Rakyat Indonesia Housing Loan or often known as KPR-BRI as a program in the field of public housing. The author chose Bank Rakyat Indonesia Tbk Pekanbaru as the object of the research location because it was based on the author's experience relating to the title, and because PT. Bank Rakyat Indonesia Tbk is a bank that is often a Financing in home loans in the city of Pekanbaru. PT. Bank Rakyat Indonesia Tbk Pekanbaru, where the authors conducted the study gave home credit with interest rates of 5.61% (2 years fixed rate) in 2018, and interest at 6.50% (1year fixed rate) in 2019.The problems examined in this study are: First, How is the implementation of a mortgage agreement at PT. Bank Rakyat Indonesia Tbk Pekanbaru? Second, Are the factors causing debtors to choose auction efforts compared to non-litigation at PT. Bank Rakyat Indonesia Tbk Pekanbaru? Third, how is the settlement of bad credit in a home ownership loan agreement between a customer and PT. Bank Rakyat Indonesia Tbk Pekanbaru?This type of research is sociological legal research. Data sources used are primary data and secondary data, data collection techniques using interviews and library studies. In this study the authors used analysis qualitatively, in drawing conclusions using inductive thinking methods.The results of this study are First, Implementing credit granting processes, prospective debtors must meet with housing developers who want to buy, then determine housing units, and determine the Bank to be used as a creditor. Third, the settlement of bad loans in a housing loan agreement between customers and PT. Bank Rakyat Indonesia Tbk, namely rescheduling, mediation, credit restructuring, good faith by customers.Keywords: Rescheduling - Agreement - Home Ownership Loans - Bad Credit - PT.Bank Rakyat Indonesia. Tbk